The Chilean Government’s Attempt to Reform and Close Cárcel Ex-Penitenciaría (CDP Santiago Sur): ¿Mientras más cambian las cosas, más se mantienen igual? - Ross, Jeffrey Ian (International criminal justice review, 2019)
Over the past decade, many South and Latin American countries have experienced an increase in crime. As a response, these states have experimented with a number of crime control methods. One of the traditional responses has been an overreliance on incarceration. Despite changes in other aspects of the Chilean bureaucracy, the prison system has lagged behind. This study explores the reasons why Cárcel Ex-Penitenciaría (CDP Santiago Sur), located in Santiago, Chile, one of the oldest operating prisons in the country, that houses the highest number of inmates, under deplorable conditions, still remains open. The article reviews the history of attempts to reform and close the facility, in the context of attempts to change national prison policy and practices and why the Penitenciaría still remains operational. It concludes with an examination why attempts to reform the prison facility have largely failed and why it remains open.